INDEPENDENT NATIONAL ELECTORAL COMMISSION AND THE CHALLENGES OF ELECTION ADMINISTRATION IN NIGERIA - Adie, Agboh Jeremiah (University of Nigeria Journal of Political Economy, 2026)
Election administration has traditionally been the responsibility of Nigeria’s election management body, the Independent National Electoral Commission (INEC). However, a critical question remains: Is INEC truly independent? Nigerians aspire to an electoral process that reflects the will of the people, one that is free, fair, transparent, and devoid of violence, maladministration, and controversy. Assessing the extent to which these aspirations are realised requires an examination of the challenges faced by INEC in administering elections. This paper explores the difficulties encountered by INEC in conducting elections in Nigeria. The study adopts the Marxist theory of the state as its analytical framework and employs both primary and secondary data sources, with qualitative analysis. The findings reveal that INEC’s administrative capacity significantly impacts election credibility. Although the commission is officially designated as independent, it lacks the operational autonomy necessary to ensure truly free, fair, and credible elections. The paper argues that structural and systemic constraints hinder INEC’s effectiveness. To address these challenges, it recommends genuine independence for the electoral body, including both financial and operational autonomy.